Recent Advances in Homogeneous Integration of Emitting Structures on a Silicon Platform - Michael Kovalev; Ivan Podlesnykh; George Krasin; Nikita Dolzhenko; Sergey Kudryashov (Photonics)
The development of planar integrated systems using silicon as the main material for the near-infrared spectral region is an important area of research due to its favourable properties, such as high compatibility with existing CMOS semiconductor technology and economic efficiency. However, the indirect bandgap of silicon (Eg = 1.12 eV) poses difficulties for efficient inter-band emission, requiring innovative approaches to the integration of light-emitting devices on silicon platforms. One of the main strategies to overcome the limitations of silicon for light emission consists of heterogeneous integration methods, including the use of quantum cascade structures and narrow-gap semiconductors, as well as non-linear light generation. However, these methods are often associated with serious drawbacks, such as fabrication complexity and integration problems, which can hinder the achievement of scalability and reliability. This paper presents a comprehensive review of existing approaches for homogeneous integration of light sources on a silicon platform. Future research should focus on optimising these integration methods to maximise the potential of silicon in the near-infrared spectrum.